The Role of Halal Ecosystem Goods in The Horn of Africa (HOA) - Samsam Ismail Hassan (Westscience Press, 2023)
The Horn of Africa (HoA) is a region with diverse cultures and traditions, and a significant Muslim population. Halal ecosystem goods have the potential to accelerate economic growth and improve the quality of life for individuals and communities in the region. This qualitative research paper aims to explore the adaptability and effectiveness of halal ecosystem goods in the HoA region, and their implications for economic growth. The study will utilize qualitative methods such as literature reviews, document analysis, and in-depth interviews with key stakeholders. The research will uncover the factors that contribute to the growth of halal ecosystem goods in the region, including their adaptability to local contexts, effectiveness in meeting consumer demand, and impact on the quality of life for individuals and communities. The findings will also identify challenges and opportunities for further development of halal ecosystem goods in the region, and provide recommendations for policymakers, businesses, and other stakeholders to foster sustainable economic growth through halal economies.